Islamic-Hindu Ecotheology in Maintaining the Sustainability of Nature in Taman Nasional Bromo Tengger-Semeru (TNBTS) - Habib, Moch. Tohiri; Rahmatullah, Asep (Al-Jadwa: Jurnal Studi Islam, 2025)
As a scientific discipline, ecotheology is important to practice in everyday life. The research tries to photograph Islamic-Hindu ecotheology in preserving nature in the Bromo Tengger Semeru national park. This research aims to explore the role of religious ethics in maintaining natural sustainability. This research uses a qualitative-descriptive method. This research concludes, first, that the formation of Islamic-Hindu ecotheology is actually more tied to cultural factors that are strongly attached to the Tengger tribe. Second, maximizing the potential of ecotheology in relation to protecting nature and the surrounding/supporting environment of TNBTS because in this case, both Islam and Hinduism as the majority religions in the communities around TNBTS have the same enthusiasm and concern for nature and the environment. Third, the Islamic-Hindu Ecotheology model in maintaining natural sustainability in TNBTS is more of a model of integrating religion with local culture. The contribution of this research lies in the affirmation of an ecotheological model that harmonizes local culture and religious values ​​as an optimal effort in nature conservation in TNBTS, providing new insights into the integration of spirituality and tradition in the context of environmental sustainability.